Comparison of vitamin c levels in dutch eggplant (Solanum betaceum Cav.) based on fruit ripeness stages - Nofiandi, Dedi; Rasyid, Roslinda; Azyenella, Lola; Arrazaq, Afif (PT WIM Solusi Prima, 2025)
Dutch eggplant or tamarillo (Solanum betaceum Cav.) is a fruit native to the Amazon region of South America that was introduced to Indonesia by Dutch colonists. This fruit contains rich nutritional compounds including proteins, carbohydrates, fats, fiber, phenolic compounds, flavonoids, carotenoids, and vitamin C. This study aimed to determine and compare vitamin C levels in Dutch eggplant fruits at different maturity stages (unripe, semi-ripe, and ripe). Quantitative analysis was performed using UV-Vis Spectrophotometry at 266.5 nm wavelength. The results showed that vitamin C content in unripe samples was 5.906 mg/100g, semi-ripe samples contained 15.518 mg/100g, and ripe samples had 22.031 mg/100g. Statistical analysis using one-way ANOVA (SPSS 25.00) revealed significant differences (p<0.05) in vitamin C levels among the three maturity stages. This research demonstrates that ripeness stage significantly affects the vitamin C content in Dutch eggplant fruits, with fully ripe fruits containing the highest levels of vitamin C.